1987
DOI: 10.1038/bjc.1987.52
|View full text |Cite
|
Sign up to set email alerts
|

Liver tumour blood flow and responses to arterial embolization measured by dynamic hepatic scintigraphy

Abstract: Summary Liver and tumour blood flow has been studied in 30 patients with multiple liver metastases and in 14 patients with solitary liver tumours by means of dynamic hepatic scintigraphy. Observations were compared with those of a group of 33 control subjects. Haemodynamic changes were also measured in 10 patients who underwent hepatic arterial embolization (HAE).The mesenteric fraction (MF) to tumour regions in 32 subjects showed a wide range compared with control subjects. In 9 patients the MF to the tumour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A reduction in the MF of specific.tumour regions of interest compared to neighbouring 'normal' liver regions in the same patients with hepatic tumours, or to liver regions in a control group has previously been reported (Flowerdew et al, 1987). An increased arterial index for the maximal liver ROI that can be investigated has also been reported in tumour-bearing liver (Leveson et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in the MF of specific.tumour regions of interest compared to neighbouring 'normal' liver regions in the same patients with hepatic tumours, or to liver regions in a control group has previously been reported (Flowerdew et al, 1987). An increased arterial index for the maximal liver ROI that can be investigated has also been reported in tumour-bearing liver (Leveson et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…After hepatic artery occlusion there is a compensation of liver tumour blood flow from the portal bed [7,19]. Clinical studies with angiography revealed a rearterialization of the liver 4 days after HAL or dearterialization [ 20,2 1 1.…”
Section: Introductionmentioning
confidence: 99%